Glutathione Synthesis Regulated by CtrA Protects Ehrlichia chaffeensis From Host Cell Oxidative Stress - Yan, Jiaqi; Liang, Qi’an; Chai, Zhouyi; Duan, Nan; Li, Xiaoxiao; Liu, Yajing; Yang, Nan; Li, Meifang; Jin, Yongxin; Bai, Fang; Wu, Weihui; Cheng, Zhihui (Frontiers in Microbiology, 2022)
Ehrlichia chaffeensis, a small gram-negative obligatory intracellular bacterium, infects human monocytes or macrophages and causes human monocytic ehrlichiosis, one of the most prevalent, life-threatening emerging zoonoses. Reactive oxygen species are produced by the host immune cells in response to bacterial infections. The mechanisms exploited by E. chaffeensis to resist oxidative stress have not been comprehensively demonstrated. Here, we found that E. chaffeensis encodes two functional enzymes, GshA and GshB, to synthesize glutathione that confers E. chaffeensis the oxidative stress resistance, and that the expression of gshA and gshB is upregulated by CtrA, a global transcriptional regulator, upon oxidative stress. We found that in E. chaffeensis the expression of gshA and gshB was upregulated upon oxidative stress using quantitative RT-PCR. E. chaffeensis GshA or GshB restored the ability of Pseudomonas aeruginosa GshA or GshB mutant to cope with oxidative stress, respectively. Recombinant E. chaffeensis CtrA directly bound to the promoters of gshA and gshB determined with electrophoretic mobility shift assay, and activated the expression of gshA and gshB determined with reporter assay. Peptide nucleic acid transfection of E. chaffeensis, which reduced the CtrA protein level, inhibited the oxidative stress-induced upregulation of gshA and gshB. Our findings provide insights into the function and regulation of two enzymes critical for E. chaffeensis resistance to oxidative stress and may deepen our understanding of E. chaffeensis pathogenesis and adaptation in hosts.